ETHNIC IDENTITY, MEMORY, AND USE OF THE PAST IN ITALYS DARK AGES - Berto, Luigi Andrea. ([S.l.])
1 online resource
Keywords: This volume examines the Italian peninsula in the early Middle Ages by focusing on research fields such as ethnic identity, memory, and use of the past. Particular attention is devoted to the way some authors were influenced by their own present' in their reconstruction of the past. The political and cultural fragmentation of Italy during the early Middles Ages, created by the Lombards' invasion of a part of the Peninsula in the late-sixth century and early-seventh century, Charlemagne's conquest of a part of the Lombard Kingdom in 774, and by the weakening of the Byzantine Empire in the eighth and ninth centuries, make this part of Europe a special area for exploring continuities and discontinuities between the Roman and the post-Roman periods in Western Europe. Across the volume, Berto examines the problems that thefeatures of primary sources and their scarcity pose to their interpretations. Ethnic Identity, Memory, and Use of the Past in Italy's Dark Ages' is the ideal resource for upper level undergraduates, postgraduates, and scholars interested in the relationship between Italy and Europe during the Middle Ages.